Educação e Escola na Base Nacional Comum Curricular: Análise a partir da Pedagogia Histórico-Crítica - TANIA APARECIDA DE PAULA (2022)
This study, which is a qualitative research, of a theoretical nature, points out important considerations that aim to analyze the concept of education and school present in the BNCC, in the elementary school stage, in the initial series, considering that it is the document that regulates the reformulation of National Common Curriculum Base in the country. The BNCC, formulated through the theoretical propositions of the Pedagogies of “Learn to learn” disseminates a conception of education and school articulated to the interests of the ruling class, and that acts directly in the orientation of the school curriculum, unconcerned with the integrality of the real formation of the individual. Through the contributions of Historical-Critical Pedagogy and its conception of education and school, the following specific goals are highlighted in this work: clarify the educational dimension from the analysis of its origin, nature and social function, in articulation to the process of human self-constitution; contextualize and analyze the theoretical foundation of the BNCC educational policy; finally, confront the BNCC and its conception of education and school in the light of Historical-Critical Pedagogy. The following methodological procedures stand out: bibliographic review and immanent documentary reading. At first, we seek to understand human formation through the centrality of work and its articulation with the ontological origin and nature of education. Then, it is intended to contribute to the understanding of the importance of school education for human formation and its defense through the elaborations of Historical-Critical Pedagogy. Finally, the documentary analysis of the BNCC, in its articulation to the pedagogies of “Learn to learn”, allowing it to conclude whether it is pertinent to understand the conception of school adopted by the pedagogy of the competences that guides the document in question. This analysis demonstrated the emptying of the contents considered essential to the process of apprehension and formation of the authentic human needs of individuals, which must be provided through school education. Therefore, from the confrontation of the BNCC with Historical-Critical Pedagogy, it was concluded that BNCC politics is expressed ineffective to what it is proposed, since there is no favorable support to the interests of a real human formation of quality and commitment to the overcoming exploitation and segregation of knowledge. Keywords: Common National Curriculum Base; Learn to learn; Historical-Critical Pedagogy.